3D Metallic Structures: A Review on Micro/Nanoforming to Fabricate 3D Metallic Structures (Adv. Mater. 6/2021). Issue 6 (9th February 2021) - Xu, Jie; Wang, Xinwei; Wang, Chuanjie; Yuan, Lin; Chen, Wanji; Bao, Jianxing; Su, Qian; Xu, Zhenhai; Wang, Chunju; Wang, Zhenlong; Shan, Debin; Guo, Bin
Abstract : In article number 2000893, Debin Shan, Bin Guo, and co‐workers survey the recent progress of micro/nano forming techniques for fabricating 3D metallic structures. The complex interplay among the factors that influence the so‐called size effect occurs in terms of materials, processes, tools and machines during micro/nano forming. High energies of the physical (electrical, ultrasonic, magnetic, thermal, etc.) fields directly/indirectly act on material aggregation, transfer, absorption, and conversion in multiscale structures, producing multiscale 3D metallic structures of high quality with great application potential in microelectronics, aerospace, automotive, and medical engineering.